Assessing Kindergarten Teachers' Competence in Integrating Character Education into Lesson Plans - Istiana, Yuyun; Dhieni , Nurbiana; Supena, Asep (Exploration in Early Childhood Research, 2024)
This study aims to develop a conceptual framework and a preliminary assessment instrument to measure kindergarten teachers' competence in integrating character education into their lesson plans. Character education, the deliberate cultivation of positive ethical and moral values in students, is increasingly recognized as essential for holistic child development. However, there is a lack of standardized tools to evaluate teachers' abilities in this domain. This research will employ a comprehensive literature review to identify the key components of teacher competence in character education lesson planning. The review will examine existing research, theoretical frameworks, and best practices in character education and early childhood pedagogy. The findings will inform the development of a conceptual framework that outlines the knowledge, skills, and dispositions necessary for effective character education lesson planning in kindergarten. Based on this framework, a preliminary assessment instrument will be designed. The expected outcome of this study is a preliminary assessment instrument grounded in a robust conceptual framework. This instrument will be ready for further refinement and validation through pilot testing and feedback from experts and practitioners in the field. This study will contribute to the field of early childhood education by providing a foundation for developing a standardized tool to evaluate and enhance teacher competence in character education, ultimately leading to improved character development outcomes for young children.